Optimalisasi Biaya Distribusi Es Batu dan Es Balok PT Prima Maesa Putra dengan Metode Transportasi - Destria Putri Widyaningrum; Palupi Qurrota’ayun; Nabila Sastika Ellyana; Nindya Rachmawati Ningsih; Titis Purwaningrum (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
The distribution of ice cubes and ice blocks is a crucial aspect of business operations, particularly in tropical climates like Indonesia. Efficient distribution is directly linked to profitability. PT Prima Maesa Putra, a producer and distributor of these products, is focused on optimizing distribution costs. Transportation methods provide a valuable tool for minimizing delivery expenses from factories to their destinations. This can be achieved by, for instance, analyzing using the North-West Corner (NWC) method and Vogel's Approximation Method (VAM) to establish initial solutions. These solutions are then evaluated using the Modified Distribution Method (MODI), yielding a total Rp 14.130.000,